1983
DOI: 10.1002/aic.690290114
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of particles in a liquid‐solids fluidized bed

Abstract: The mechanics of particle motion in a fluidized bed were studied by focusing on the microscopic behavior of the particles. The local displacements of nylon particles fluidized by liquid were measured by the microcapacitance method, and the resultant time series was analyzed by determining its auto-correlation function and the corresponding power spectrum. This has given rise to a stochastic or statistical model of particle displacements in the fluidized bed. This model visualizes the particle motion in a fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Their unique features are the effective liquid-solid contact and the high rates of heat and mass transfer (Morooka et al, 1980;Muroyama et al, 1986;Kang and Kim, 1987). Nevertheless, the performance of a liquidsolid fluidized bed as a contactor or reactor is influenced appreciably by various factors, such as the flow regime (Volpicelli et al, 1966;Kang and Kim, 1988), the motion of fluidized particles (Handley et al, 1966;Kmiec, 1978;Yutani et al, 1983), and voidage distribution (Fan et al, 1985); this gives rise to highly complicated, nonlinear and stochastic behavior of the bed. While some attempts had been made to stochastically analyze and model such behavior, they were mostly based on the Markovian assumptions and notion of classical Brownian motion (Yutani et al, 1982(Yutani et al, , 1983Yutani and Fan, 1985;Fan et al, 1990a;Kang et al, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their unique features are the effective liquid-solid contact and the high rates of heat and mass transfer (Morooka et al, 1980;Muroyama et al, 1986;Kang and Kim, 1987). Nevertheless, the performance of a liquidsolid fluidized bed as a contactor or reactor is influenced appreciably by various factors, such as the flow regime (Volpicelli et al, 1966;Kang and Kim, 1988), the motion of fluidized particles (Handley et al, 1966;Kmiec, 1978;Yutani et al, 1983), and voidage distribution (Fan et al, 1985); this gives rise to highly complicated, nonlinear and stochastic behavior of the bed. While some attempts had been made to stochastically analyze and model such behavior, they were mostly based on the Markovian assumptions and notion of classical Brownian motion (Yutani et al, 1982(Yutani et al, , 1983Yutani and Fan, 1985;Fan et al, 1990a;Kang et al, 1990).…”
mentioning
confidence: 99%
“…Nevertheless, the performance of a liquidsolid fluidized bed as a contactor or reactor is influenced appreciably by various factors, such as the flow regime (Volpicelli et al, 1966;Kang and Kim, 1988), the motion of fluidized particles (Handley et al, 1966;Kmiec, 1978;Yutani et al, 1983), and voidage distribution (Fan et al, 1985); this gives rise to highly complicated, nonlinear and stochastic behavior of the bed. While some attempts had been made to stochastically analyze and model such behavior, they were mostly based on the Markovian assumptions and notion of classical Brownian motion (Yutani et al, 1982(Yutani et al, , 1983Yutani and Fan, 1985;Fan et al, 1990a;Kang et al, 1990).Our recent works on multiphase flow systems (Fan et al, 1989(Fan et al, , 1990b have indicated that the concept of fractional Brownian motion (fBm), which can be characterized by the Hunt exponent, H , may be applicable to the analysis of liquidsolid fluidized beds. The model based on this concept has been proposed by Mandelbrot and van Ness (1968) to identify the long-term correlation in a time series, which is self-affine.…”
mentioning
confidence: 99%
“…The resultant autocorrelation and power spectral density functions were then used to determine the frequency of the fluctuations. Among the stochastic models, one of the most notable has been the model proposed by Yutani et al (1983). Both Yutani et al (1983) and more recently Neogi et al (1988) have considered that any of the pressure fluctuation signals from fluidized beds consists of two components, a periodic component, and a random component; the latter is modeled as a continuous-time Markov process.…”
Section: Introductionmentioning
confidence: 99%
“…Our exhaustive review of the available data and the results of our experiments have indicated that the time series of pressure fluctuation signals from a fluidized bed exhibits long-term correlation similar to that observed in many hydrological time series. So far the Markov processes, including the Brownian motion, have played dominant roles in modeling the pressure fluctuations in fluidized beds (see, e.g., Yutani et al, 1983;Neogi et a!., 1988). Nevertheless, they tend to underestimate long-term trends such as the range of "cumulative departure" from the mean as suggested by Hurst (1956).…”
Section: Introductionmentioning
confidence: 99%
“…
The performance of a liquid-solid fluidized bed is substantially influenced by various mutually interacting factors, such as flow regime, motion of fluidized particles, and voidage distribution; this gives rise to highly complicated, nonlinear and/or stochastic behavior of the bed. While some attempts had been made to stochastically analyze and model such behavior, they were based mostly on the Markovian assumptions and notion of classical Brownian motion (Yutani et al, 1983;Yutani and Fan, 1985;Fan et al, 1995).Recent works on multiphase flow systems demonstrated that some of the phenomena taking place in liquid-solid fluidized beds are amenable to the analysis couched in the parlance of the fractional Brownian motion (Bm) characterized by the Hurst exponent H or equivalently the local fractal dimension d,, (Feder, 1988;Fan et al, 1990bFan et al, , 1993. The model based on this concept was proposed originally by Mandelbrot and van Ness (1968) to identify the long-term correlation in a self-affine time series.
…”
mentioning
confidence: 99%